A ESTIGMATIZAÇÃO DE MULHERES VÍTIMAS DE VIOLÊNCIA SOB UMA PERSPECTIVA SOCIOINTERACIONAL A PARTIR DE SEUS RELATOS ORAIS - Fernanda Camargo Aquino (2022)
In this research, we investigate, by means of the interface between language and society, the impact of gender violence on the stigmatization of women who suffered domestic violence before and during the COVID-19 pandemic. The general aim of this work is to analyze the oral personal reports spontaneously produced by those women in order to verify how the attributes that differentiate them in their relationships contribute to the construction of the stigma of violence in the domestic and family context. The specific objectives are: to describe how politeness and facework are employed by them to construct a new social identity due to the violence; to establish relations between facework and politeness strategies through the study of social stigma; and, finally, to identify the linguistic resources that are recurrent in the oral reports of women victims of abuse, analyzing the meaning effects produced by the functional behavior of these resources in the specific context of domestic and family violence. This work is mainly based on the theoretical framework of Conversation Analysis (CA), in a socio-interactional perspective, and the corpus is composed of oral reports of 13 victims who suffered violence from their intimate partners, typified in the Maria da Penha Law (BRASIL, 2006), selected on the world wide web, with public access, in the period between 2019 and 2021, and transcribed according to Preti (2002). The findings show that there was a threat to the victim’s face, since the aggressor partner invades the woman’s individual territory. Regarding politeness rules, we observe that there was no intention, in the women’s statements, to promote disagreements or generate confrontations in the interaction. We highlight, however, that the speakers tried to employ politeness procedures in order to spare their aggressors, mitigating confrontational situations in interactions that could threaten their partners’ face. Thus, all the points listed above collaborated directly with the partner’s intentional desire to humiliate the woman, diminishing her existence and preventing her from living with dignity, cooperating, therefore, to establish and strengthen the stigma of violence. Keywords: Conversation Analysis; Language; Verbal Interaction; Social Stigma; Violence against Women.